Start-Up Daerah Wisata Melalui Edukasi dan Manajemen Sampah di Kampung Pelangi - Melvin Carrie; Derwin Gallen; Alessandro Del Piero; Ellen Engelica; Kenny Ogusstianto; Dessy Karlina; Jenny June; Ho Gefi Lee (National Conference for Community Service Project (NaCosPro), 2019)
Kampung Pelangi is one of the tourist villages that are in Tanjung Uma, Batam. The creation of Kampung Pelangi that is filled with colors begins with a simple idea, but as time goes by, this idea that was just an idea has become a reality that is pioneered by one of the members of Baitul Maal was Tamwil (BMT) Seri Pelangi Kepri. The problem that we found from our research is the place that is used as a tourism spot has a lot of garbage around it, and because of that, it reduce the beauty of the tourism spot itself. The purpose of this research is to make garbage bins around the area of the tourism spot and educate the public so that Kampung Pelangi can be more beautiful and comfortable in the eyes of local residents as well as foreigners. The method that we use in this research is a qualitative study design with observational descriptive. Then there are also assessment techniques that are carried out by field survey, group discussion that involves participants, open interview, and literature study. The result from our research proves that the activities that we do together in the area produced a very satisfying result, because of the teamwork and helping each other.